Legal Protection of Consortium Agreement Deeds by Notaries in Infrastructure Projects in Indonesia - Kurnianto, Baputera; Shallman, Shallman (TABELLIUS: Journal of Law, 2025)
Abstract. Indonesia, as a developing country with increasing economic growth, requires adequate infrastructure development to support progress in various sectors, such as transportation, energy, telecommunications, and others. Various infrastructure development efforts are funded and implemented by various projects involving consortia. However, in practice, the implementation of infrastructure projects involving consortia often encounters obstacles in the matter of legal protection of the consortium agreement itself. Therefore, this study aims to identify the form of legal protection of the consortium agreement deed by a notary in infrastructure projects in Indonesia. The research method used is a qualitative approach with a descriptive analytical research type, which aims to obtain data in depth and analyze it comprehensively. Data were obtained through literature studies and interviews with related parties, including notaries, business actors, and legal experts. The results of the study indicate that the deed of consortium agreement prepared by a notary has binding legal force, but there are several challenges related to the lack of supervision of notary practices and the ambiguity in several clauses of the agreement that can cause disputes.Keywords: Agreement; Consortium; Legal; Protection.